Complete Genome Sequence of Klebsiella pneumoniae Strain TK421, a Conjugative Hypervirulent Isolate - Kochan, Travis J. (Microbiol Resour Announc, 2020)
Klebsiella pneumoniae is a Gram-negative bacterium that is a major cause of nosocomial infections worldwide. Here, we present the complete genome sequence of TK421, a clinical bacteremia isolate containing a hypervirulence plasmid carrying tra-associated conjugation machinery genes. Emergence of conjugative hypervirulence plasmids could portend rapid dissemination of hypervirulence among multidrug-resistant K. pneumoniae strains.